Cytotoxicity in the frog (Fejervarya limnocharis) after acute cadmium exposure in vivo. Issue 6 (2nd November 2018) - Boonmee, Sirilak; Thitiyan, Thitaporn; Tanomtong, Alongklod; Tengjaroenkul, Bundit; Neeratanaphan, Lamyai
Abstract: Chromosome aberrations (CA) in frogs ( Fejervarya limnocharis ) exposed to 5, 10 and 20 mg/L of cadmium chloride (CdCl2 ) for 24, 48 and 72 h were invetegated. Treated frogs were compared to a control group. Cadmium (Cd) was not detected in the water or control frogs. The highest Cd concentrations in water and frog samples were found at 20 mg/L exposed for 72 h. The water samples indicated that exposure to 10 mg/L of Cd for 24 h was significantly different from the control ( p  < 0.05). Cd concentrations in frogs differed significantly between the control and experimental groups ( p  < 0.05). The cytotoxicity assessment revealed ten types of CA in the frogs, including single chromatid gap (SCG), isochromatid gap, single chromatid break, isochromatid break, iso-arm fragmentation, single chromatid decomposition, centric fragmentation, centromere gap, deletion and fragmentation. The most common CA in the study was SCG. The statistical analysis indicated significant differences in the percentage of cells with CA for exposures of 20 mg/L (24 h), 10 and 20 mg/L (48 h) and 5, 10 and 20 mg/L (72 h) compared to the control ( p  < 0.05). The results of this study show that high Cd concentrations and long duration exposure can cause CA in frogs.